2010
DOI: 10.1103/physrevb.81.094416
|View full text |Cite
|
Sign up to set email alerts
|

Quantized spin-wave modes in magnetic tunnel junction nanopillars

Abstract: We present an experimental and theoretical study of the magnetic field dependence of the mode frequency of thermally excited spin waves in rectangular shaped nanopillars of lateral sizes 60 × 100, 75 × 150, and 105 × 190 nm 2 , patterned from MgO-based magnetic tunnel junctions. The spin wave frequencies were measured using spectrally resolved electrical noise measurements. In all spectra, several independent quantized spin wave modes have been observed and could be identified as eigenexcitations of the free l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 42 publications
4
31
0
1
Order By: Relevance
“…5(a) shows that our simulations are in a good agreement with the measured 30 dependence of frequency on current for A Py between 0.6×10 -6 erg/cm and 0.65×10 -6 erg/cm (and A CoFe = 3×10 -6 erg/cm, M CoFe = 1800 emu/cm 3 ). The relatively low value of the Py exchange stiffness required to achieve this agreement is not surprising 41 , considering that the saturation magnetization of the alloy used in the real device is also low (M Py = 580 emu/cm 3 ). Here we also note that the same low value of A Py is necessary to achieve the satisfactory agreement for the magnetoresistance hysteresis loops (see Sec.…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…5(a) shows that our simulations are in a good agreement with the measured 30 dependence of frequency on current for A Py between 0.6×10 -6 erg/cm and 0.65×10 -6 erg/cm (and A CoFe = 3×10 -6 erg/cm, M CoFe = 1800 emu/cm 3 ). The relatively low value of the Py exchange stiffness required to achieve this agreement is not surprising 41 , considering that the saturation magnetization of the alloy used in the real device is also low (M Py = 580 emu/cm 3 ). Here we also note that the same low value of A Py is necessary to achieve the satisfactory agreement for the magnetoresistance hysteresis loops (see Sec.…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…The mutual spin transfer torque is found to play a minor role, which in our case translates only into a small reduction of the current required to observe the effect. The fact that it is an effect mediated by dipolar interaction may seem reminiscent of the mode splitting occurring when two linear modes interact through dipolar coupling 17 . However, it should be pointed out that the jump in the frequency of the steady state mode 2 due to interaction with mode 3 is not observed when the two modes are linear modes or when the precession amplitude of the steady state mode 2 is low (at lower current, see Fig.…”
Section: Non-linear Interactionmentioning
confidence: 99%
“…However, important questions remain open and many features observed experimentally cannot be explained in the frame of this 'independent free layer' picture. Recent investigations have addressed the coupling between the different magnetic layers of an STO and demonstrated that it strongly impacts the excitations spectra [6][7][8][9][10][11][12][13][14][15][16][17][18] , and that it can be exploited in the interest of the device performances [7][8][9][10] .…”
mentioning
confidence: 99%
“…The origin of this double resonance mode is not entirely clear. In previous publications, it has been attributed to domain formation in the FL, 15 higher-order spin wave excitations, 16 and magnetization precession in other layers of spin-valve MTJs. 17 To analyze the double resonance mode in sample S3 in more detail, we performed macrospin simulations using the model presented in Ref.…”
Section: A St-fmrmentioning
confidence: 99%